Sociodemographic factors associated with waist circumference among male and female adults: findings of the Malaysian adult nutrition survey 2014 - Yong, Kang Cheah; Omar, Mohd Azahadi; Mohamad Nor, Noor Safiza; Siew, Nooi Phang; Abd. Manaf, Noor Hazilah (Universiti Putra Malaysia Press, 2020)
Introduction: This study examined how waist circumference (WC) varied across sociodemographic characteristics of Malaysian adults using a nationally representative data. Methods: Data from the Malaysian Adult Nutrition Survey 2014 (n = 2696) was used. In the sample, 46.55% were males and 53.45% were females. The outcome variable was WC. Waist circumference was categorised into four ordinal outcomes: Very low, low, high and very high. The explanatory variables were age, monthly individual income, education, gender, marital status, ethnicity, employment status and household location. Ordered probit models were utilised. Results: The majority of males had a low WC (54.66%), and only a small proportion had a very high WC (0.96%). Similarly, a high proportion of females had a low WC (55.59%), and only 1.94% had a very high WC. Younger males were more likely to have a high WC than their older counterparts. Males who had monthly income of RM2000-2999 or RM3000-3999 were more likely to have a high WC compared with those who had monthly income of ≤RM999. Chinese and Indian males were more likely to have a high WC than Bumiputera males. For females, those who were married, widowed/divorced and Bumiputera were likely to have a high WC. Conclusion: WC was associated with various sociodemographic profiles of males and females. In particular, there were positive associations between the likelihoods of having a high WC and younger age group, higher income, Chinese, Indian, and being married. Our findings provided policy makers with better information on formulating intervention measures